Karakterisasi Serbuk Timah dari Sistem Atomisasi Gas Argon Panas - Sub Sistem Gas Alir Tabung Gas - Basyir, Abdul; Aryanto, Didik; Jayadi, Jayadi; Widayatno, Wahyu Bambang; Wismogroho, Agus Sukarto (Jurnal Rekayasa Mesin, 2021)
The tin powder was used in some applications and technology such as for part manufacture through alloying, pressing, and sintering process, mixing material for the pyrotechnic application, the main material for solder pasta, mixing material on tin chemical, and others. Therefore, the demand for tin powder with a small size, spherical shape, and high purity is increasing severely. Indonesia (PT. Timah Tbk.) is one of the world’s largest producers of tin raw materials. This raw material can be processed be as powder by the atomization method. In this research, hot argon gas atomization system was used to generated tin powder. Raw tin was melted in a melting chamber with temperature variations of 600, 700, 800, and 900 °C. This experiment generates powder with a dominant size of 37 – 150 mm. Meanwhile, for size powder of 0 – 30 mm, dominated by size range of 0 – 10 mm. Furthermore, the size powder of 0 – 30 mm is composed of tin phase, without tin oxide. The tin powder of melting chamber temperature of 900 °C produces the largest tin powder with a size of 0 – 10 mm and spherical powder.